PENDIDIKAN AKHLAK PADA ANAK TUNALARAS DI SEKOLAH LUAR BIASA PRAYUWANA YOGYAKARTA - La Ode Yarfin; Suyadi (Universitas Muhammadiyah Prof Dr Hamka, 2020)
Islamic religious education is a right for all children, including children with special needs, especially disability or disorder of social disorders and deviant behavior. These conditions require a new approach in Islamic religious education, thus forming a noble. The purpose of this study was to analyze the moral education of children with physical impairment in E Prayuwana Special School (SLB) Yogyakarta. This research approach is qualitative in the form of descriptive analysis. The subjects of this study were 4 children with grades 2, 3, 4 and 5 Elementary / SLB and one Teacher of Islamic Education. Data collection techniques carried out by observation, interviews and documentation. Data analysis was performed in a descriptive and analytical way. The results showed that moral education in children with physical impairment was done by conditioning good manners, worship habits, and honest behavior.